Tourists’ Satisfaction Towards Agro-tourism In Wang Ang Subdistrict Cha-uat District Nakhon Si Thammarat Province - Intakong, Nilawan; Srisuwan, Supattra; Niyamangkoon, Surin (Journal of MCU Humanities Review, 2020)
The objectives of this research were 1. to study personal factors, travelling factors and exposure to information of tourists. 2. to study tourists’ satisfaction towards agro-Tourism. 3) to compare the tourists’ satisfaction towards agro-tourism by personal factors, travelling factors and exposure to information of tourists. The samples consisted of 331 tourists’ travel agro-tourism. Data were collected by using interviewing schedule. Statistical analyses were frequency, percentage, mean, standard deviation, minimum, maximum, t-test, Oneway Analysis of Variance and Multiple Comparison by Least Significant Difference. The result of the research revealed the hypothesis testing showed that age, education, career, objectives travelers, the travel vehicles and exposure to media persons different had in tourists’ satisfaction towards agro-tourism significant differences at the 0.01 level. Income and expenditure different had in tourists’ satisfaction towards agro-tourism significant differences at the 0.05 level. However, sexual, exposure to mass media and exposure to social media were different no in tourists’ satisfaction towards agro-tourism significant differences.